2020
DOI: 10.3389/fgene.2020.00970
|View full text |Cite
|
Sign up to set email alerts
|

Hub Genes Identification in a Murine Model of Allergic Rhinitis Based on Bioinformatics Analysis

Abstract: This study aimed to identify allergic rhinitis (AR)-related hub genes and functionally enriched pathways in a murine model. Dataset GSE52804 (including three normal controls and three AR mice) was downloaded from Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) were identified. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and protein-protein interaction (PPI) analyses of DEGs were performed to identify the hub genes in AR. The DEGs were classified into differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Some studies using bioinformatics analysis have found that CXCR2 plays an essential role in the occurrence of allergic rhinitis. 30 Eddleston et al found that CXCR1 and CXCR2 mRNA expression in patients with allergic rhinitis increased compared with baseline. 31 Previous RNA-seq of immunotherapy induced-PBMC found 1.3-fold upregulation of CXCR1 and 1.8-fold upregulation of CXCR2, and its ligands IL-8, IL-1β, and CXCL1 were also up-regulated, which was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using bioinformatics analysis have found that CXCR2 plays an essential role in the occurrence of allergic rhinitis. 30 Eddleston et al found that CXCR1 and CXCR2 mRNA expression in patients with allergic rhinitis increased compared with baseline. 31 Previous RNA-seq of immunotherapy induced-PBMC found 1.3-fold upregulation of CXCR1 and 1.8-fold upregulation of CXCR2, and its ligands IL-8, IL-1β, and CXCL1 were also up-regulated, which was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many research papers on allergen bioinformatics and immunoinformatics have been published by various groups of researchers [198,199]. For example, Zhang et al identified key genes and Le Chen et al identified hub genes in a murine model in allergic rhinitis by bioinformatics analysis [200,201]. Deocaris et al used bioinformatics analysis in the detection of nascent allergens in GMO and conventional rice [202].…”
Section: Role Of Bioinformatics In Allergic Diseases Managementmentioning
confidence: 99%
“…Based on the interconnectivity of genes, WGCNA can explore the relationships between gene modules and the clinical phenotypes to identify candidate biomarkers or therapeutic targets. It has been applied to numerous kinds of diseases (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%